SECONDARY METABOLITES EXTRACTION USING POTENT BIOLOGICALS & PHYTOCHEMICAL SCREENING - KULSHRESHTHA, AKANKSHA; RANAWAT, MAHENDRA SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Antioxidants present in the diet may have a significant effect on the prophylaxis and progression of various diseases associated with oxidative stress like cancer diabetes, cardiovascular and neurodegenerative. Berries and fungal species contain a range of secondary metabolites with antioxidant properties, including phenolic compounds. The objective of this study is to extract secondary metabolites from biologicals (wild berries and fungal species from the Himalaya region) and to conduct the preliminary phytochemical screening, total flavonoid and phenolic contents assays of various solvent extracts. In this study, wild species were collected from the Himalayan region and extracted with different solvents by Soxhlet extraction. Phytochemical screening was carried out using standard procedures, total flavonoid content was measured by the aluminum chloride colorimetric assay and total phenolic content was estimated spectrophotometrically by the Folin-Ciocalteau method. Preliminary phytochemical screening reveals that except a few all extracts show the presence of alkaloids, tannin, carbohydrate, glycosides phenol, and flavonoid. Only Water, methanolic, and Chloroform extract of Rubus indicus (RIW, RIM, RIC) and water, methanolic extract of Solanum nigrum (SNW and SNM) contains steroids. Saponins are found only in extracts of Solanum nigrum and Morchella esculenta. Water extract of Rubus armeniacus, Solanum nigrum, Morchella esculenta and methanolic extract of Rubus indicus, Lycium barbarum (RAW, SNW, MEW, RIM, and LBM) shows higher content of flavonoid and phenol. Methanolic extract of Lycium barbarum and Rubas armeniacus has the richest content of phenolics and flavonoids i.e. (102.16 mg GAE/g and 2.95 mg QE/g) respectively, on the contrary, hexane extract of Morchella esculenta and chloroform extract of Lycium arbarum was the least i.e. (6.64 mg GAE/g and 0.59 mg QE/g). All the extracts were not significantly different from one another (p > 0.05). It can be hypothesized that the high contents of phenolic compounds of these sample extracts indicated that these compounds contribute to the antioxidant activity and can be regarded as promising plant species for natural sources of radical scavenging activity with potential value for the treatment of many life-threatening diseases.